Cannabis for paediatric epilepsy: challenges and conundrums. Issue 3 (19th February 2018) - Chen, Kerrie‐Anne; Farrar, Michelle A; Cardamone, Michael; Lawson, John A
Summary: Research is expanding for the use of cannabidiol as an anticonvulsant drug. The mechanism of cannabidiol in paediatric epilepsy is unclear but is thought to play a role in modulation of synaptic transmission. Evidence for its efficacy in treating epilepsy is limited but growing, with a single pharmaceutical company‐funded randomised double‐blind controlled trial in children with Dravet syndrome. Progress towards the use of medicinal cannabinoids incorporates a complex interplay of social influences and political and legal reform. Access to unregistered but available cannabidiol in Australia outside of clinical trials and compassionate access schemes is state dependent and will require Therapeutic Goods Administration approval, although the cost may be prohibitive. Further clinical trials are needed to clearly define efficacy and safety, particularly long term.